Dilema Safe Harbor: Pertanggungjawaban Marketplace terhadap Peredaran Kosmetik Overclaim dan Ilegal - Nadine Ramadhani; Faldin Abimayu; Sri Handayani (Indonesian Journal Publisher, 2026)
The rapid growth of e-commerce in Indonesia has triggered challenges regarding illegal cosmetics and overclaim practices. This study examines marketplace liability limits under the safe harbor doctrine, referenced against Consumer Protection Laws and BPOM Regulation No. 3 of 2022. The findings reveal that the safe harbor doctrine cannot serve as an absolute shield for marketplaces when they engage in omission regarding reported problematic products. The analysis concludes that the failure of algorithmic verification systems to filter misleading claims constitutes negligence and qualifies as an Unlawful Act (PMH) under Article 1365 of the Indonesian Civil Code . Consequently, real-time curation system integration between the BPOM database and marketplace platforms is essential to ensure consumer rights to honest information.